Pengaruh Hubungan Belitan Trafo Dan Variasi Beban Terhadap Total Harmonic Distortion - S, Rocky Samuel; Rosma, Iswadi Hasyim; Firdaus, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Transformers used in generator are generally 3 phase transformers. In the transformer there is a role that is to move and change the amount of electrical energy from one or more electrical circuits to another circuit. In the use of transformers, there many advantages, but there are also disadvantages such as harmonic distortion which can cause power losses and decreased working capacity. Therefore, this thesis aims to analyze the effect of transformer winding type and transformer loading conditions on the harmonic distortion. In this study used supporting tools namely resistive and induktive loads and to see the THD level using the KYORITSU 6310 Power Quality Analyzer. And the variation of the entanglement relationship used is the wye and delta relationship. The test result concluded that the relationship between wye-wye and resistive load had the highest THD percentage of 44,35% dan delta-delta relationship had the lowest THD percentage of 3.06%. Keywords : harmonics, transformators, THD, power quality analyzer.